Implicity Linear Collocation Method and Iterated Implicity Linear Collocation Method for the Numerical Solution of Hammerstein Fredholm Integral Equations on 2D Irregular Domains (Journal of Computational Mathematics, 2020)
In this work, we adapt and compare implicity linear collocation method and iteratedimplicity linear collocation method for solving nonlinear two dimensional Fredholm integralequations of Hammerstein type using IMQ-RBFs on a non-rectangular domain. IMQsshow to be the most promising RBFs for this kind of equations. The proposed methodsare mesh-free and they are independent of the geometry of domain. Convergence analysisof the proposed methods together with some benchmark examples is provided whichsupport their reliability and numerical stability.